2021
DOI: 10.1103/physrevapplied.16.034048
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Modeling of Organic Light-Emitting Diodes Containing Molecules with Large Electric Dipole Moments

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…The intriguing and highly nontrivial time dependence of emission spectra collected in several matrices is quantitatively reproduced, accounting for the subtle interplay among polar solvation dynamics, the nonadiabatic dynamics of conformational degrees of freedom fully accounting for static dielectric and conformational disorder, and the consequent inhomogeneous broadening phenomena. The model, quantitatively validated against experimental photoluminescence data collected in diluted solutions and solid matrices, sets a solid basis to account for environmental effects, including disorder, in phenomenological models for OLED devices. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intriguing and highly nontrivial time dependence of emission spectra collected in several matrices is quantitatively reproduced, accounting for the subtle interplay among polar solvation dynamics, the nonadiabatic dynamics of conformational degrees of freedom fully accounting for static dielectric and conformational disorder, and the consequent inhomogeneous broadening phenomena. The model, quantitatively validated against experimental photoluminescence data collected in diluted solutions and solid matrices, sets a solid basis to account for environmental effects, including disorder, in phenomenological models for OLED devices. , …”
Section: Introductionmentioning
confidence: 99%
“…The model, quantitatively validated against experimental photoluminescence data collected in diluted solutions and solid matrices, sets a solid basis to account for environmental effects, including disorder, in phenomenological models for OLED devices. 40,41 ■ MATERIALS AND METHODS Molecular Model. As detailed in ref 31 and shortly introduced above, we consider only two electronic basis (diabatic) singlet states, corresponding to the neutral DA state, |N⟩, and to the zwitterionic D + A − state, |Z⟩.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Meanwhile, the benefits of SOP in OLEDs are still controversial, e.g., SOP can improve charge injection efficiency and also affect charge blocking property. [ 20–24 ] Thus, exploring methods to control the charge accumulation property while keeping SOP is an important issue to optimize the device performance as well as to understand the role of SOP. In that sense, it will be intriguing to use a device stack with identical (non‐vanishing) SOP in all layers.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the benefits of SOP in OLEDs are still controversial, e.g., SOP can improve charge injection efficiency and also affect charge blocking property. [20][21][22][23][24] Thus, exploring methods to control the charge accumulation property while keeping SOP is an important issue to optimize the device performance as well as to understand the role of SOP. In that sense, it will be intriguing to use a device stack with identical It is demonstrated that dipolar doping of hole transport layers (HTLs) controls the density and polarity of the accumulated charge at the critical interface between the HTL and the emission layer (EML) in organic lightemitting diodes (OLEDs).…”
mentioning
confidence: 99%
“…Understanding the charge distributions in the vicinity of the emission layer (EML) of an organic light-emitting diode (OLED) is crucial for improving device performance. The charge distribution influences both the emission zone and the exciton-polaron quenching (EPQ) probability. Consequently, it also affects the external quantum efficiency (EQE), efficiency roll-off, and device degradation. , However, determining the charge distribution in a stacked multilayer OLED is not straightforward, and the influence of the accumulated charges on the optical properties of such a device has been controversial. For instance, the rate constant for triplet-polaron quenching (TPQ), k TP , has been examined in OLEDs as well as in hole-/electron-only devices by many groups.…”
Section: Introductionmentioning
confidence: 99%